Efisiensi Pelapisan Amilum terhadap Campuran Biochar Tongkol Jagung Dengan Pupuk NPK Melalui Metode Coating - Ndjudi, Serli Kahi; Iskandar , Taufik; Abrina Anggraini , Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
The use of biochar and NPK fertilizers in an effort to overcome the problem of inefficiency in using excessive fertilizers on the fertility of nutrients in the soil. This is because nearly 40-70% N, 80-90% P, and 50-70% K are lost to the environment without being absorbed by plants which results in leaching, degradation, and evaporation of volatile materials in the soil. The purpose of this study was to obtain the efficiency of the results of starch coating on the mixture of corncob biochar with NPK fertilizer through a coating method which functions to bind the content of biochar and NPK fertilizer which has been coated with starch in the soil so that it does not evaporate easily when exposed to sunlight and also so that fertilizer is more hold for a long time so that it is not easily carried away by water erosion. The variables determined were NPK fertilizer content of 10%, 20%, and 30% of the weight of the corncob biochar and the concentration of starch as a coating of 10%, 20%, and 30%. The results obtained in this study were the lowest percentage value of coating was obtained, namely 0.4256%, and the highest dissolution rate was obtained at 3600 seconds. The optimization value obtained in the Minitab analysis is at 10% NPK with a 30% starch concentration with a desirability value of 0.4983. Thus, it can be concluded that the efficiency of starch coating on biochar greatly affects the percent coating and the resulting dissolution rate.